Theory of value and money based on Thomas Aquinas - Csocsán de Várallja, Eugene (Verbum – Analecta Neolatina, 2005)
The market pulsates in the teleological dynamism of the economy. The price formations of the market focus on the problem of value. The various goods obtain a common denominator in value judgements through the three stages of evaluation. At the first stage in the ontological base constituted by the analogia proportionis of utility, reason, the mind, can recognise the teleological relationship. At the second stage in this light of aims, reason can appreciate the value relationships in the items' rarity compared with the goals proposed. At the third stage, reason compares the possibilities of means with the aims which count to the person's will, and the various disparate items become of equal value by the decision of the will, in which the standard is the virtue of prudence. Economic value is measured by money, which is the product of the human society's will following our reason, as the society of monkeys lacks money. Money is such a tool of measuring economic value by which we might acquire anything according to its measure, as it is a draft on the national product constituting its real matter in the Aristotelian sense.